SOLVING FREDHOLM INTEGRAL EQUATION VIA FIXED POINT THEOREM IN CONTROLLED METRIC TYPE SPACES - Bamel, A.; Sihag, V. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2025)
In this paper, we present the concepts of hesitant fuzzy mapping, contraction of hesitant fuzzy mapping, and generalized contraction of hesitant fuzzy mapping within controlled metric-type spaces. These concepts are used to establish fixed-point theorems. Finally, the results are applied to solve a Fredholm-type integral equation.